Advances in Wireless Networks and Information Systems - Luo, Qi.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This volume contains revised and extended research articles written by prominent researchers participating in WNIS 2009 conference. Topics covered include Wireless Information Networks, Wireless Networking Technologies, Mobile Software and Services, intelligent computing, network management, power engineering, control engineering, Signal and Image Processing, Machine Learning, Control Systems and Applications, The book will offer the states of arts of tremendous advances in Wireless Networks and Information Systems and also serve as an excellent reference work for researchers and graduate students working on Wireless Networks and Information Systems.
Web Services Discovery in Metric Space through Similarity Search -- An Effective Measure of Semantic Similarity -- Improved Run-Length Coding for Gray Level Images Using Gouraud Shading Method -- Factors Affecting Consumer Intentions to Acceptance Banking Services in China -- Comparative Study of Workload Control Methods for Autonomic Database System -- Consensus of Mobile Agent Systems Based on Wireless Information Networks and Pinning Control -- Dynamic Evolution in System Modeling of Knowledge-Intensive Business Services$1 (BOrganizational Inertia -- Research on Java Imaging Technology and Its Programming Framework -- The Performance of SFN in Multi-Media System -- A Domain-Oriented Goal Elaborate Method -- A Hybrid Genetic Routing Algorithm in Wireless Sensor Networks -- The Application of Fast Multipole-BEM for 3-D Elastic Contact Problem with Friction -- Simulation Method Research of Ground Target IR Scene Based on Aerospace.s
Keywords: Engineering; Information systems; Microwaves; Telecommunication; Engineering; Microwaves, RF and Optical Engineering; Communications Engineering, Networks; Information Systems and Communication Service